2022
DOI: 10.3390/f13060929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Planting, Vegetation Management, and Pre-Commercial Thinning on the Growth and Yield of Lodgepole Pine Regenerated after Harvesting in Alberta, Canada

Abstract: A large long-term field trial was established in the Upper and Lower Foothills sub-regions of the Canadian boreal forest to monitor the effects of planting, vegetation management, and pre-commercial thinning on the development of lodgepole pine stands following harvesting. Data collected at the end of the trial’s regeneration phase, 17 to 20 years after its establishment, were tested for treatment effects and projected to rotation age. Planting generally improved stocking and increased projected growth and yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…To this end, several pre-commercial [32,33] and commercial [19] thinning research trials in lodgepole pole pine have been recently initiated, largely focused on the foothill subregions in Alberta and following a more robust statistical procedure. However, the information on thinning of lodgepole pine stands gathered from current experiments in Alberta does not provide a sufficient baseline for developing a thinning practice for the species.…”
Section: The Evolving Shifts In Alberta's Stand-tending Practicesmentioning
confidence: 99%
“…To this end, several pre-commercial [32,33] and commercial [19] thinning research trials in lodgepole pole pine have been recently initiated, largely focused on the foothill subregions in Alberta and following a more robust statistical procedure. However, the information on thinning of lodgepole pine stands gathered from current experiments in Alberta does not provide a sufficient baseline for developing a thinning practice for the species.…”
Section: The Evolving Shifts In Alberta's Stand-tending Practicesmentioning
confidence: 99%
“…However, there is a pending midterm timber supply shortage in Alberta due to past natural disturbances and a shrinking forestry land base giving rise to recent research on the thinning response of lodgepole pine. Recent studies have shown the effect of thinning (both pre-commercial (PCT) and commercial thinning (CT)) on the growth and productivity of lodgepole pine at the stand level [24][25][26]. However, the thinning response of individual trees and their growth dynamics over time has not been addressed intensively, especially with different thinning intensities and combinations of PCT and CT. Thinning intensities are one of the most important factors affecting growth response after thinning [27][28][29].…”
Section: Introductionmentioning
confidence: 99%